ANALISIS PENDAPATAN USAHATANI JAGUNG DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Lahandu, Sumiati A.; Antara, Made; Muis, Abdul (AGROTEKBIS, 2016)
The research aimed to determine the income of corn farming system in Labuan Toposo village, Labuan Sub-District of Donggala District. This research located in Labuan Toposo Village, Labuan Sub-District of Donggala District and conducted from March to May 2015. Respondents were chosen using a Simple Random Sampling technique. The number of the respondents was 34 people selected from 150 corn farmers. Data was analyzed using the Income analysis. The research results showed that the production of the corn farming system is IDR 3,932/kg per one planting season and the average revenue is IDR 15,729,412/ha. With the average total cost of IDR 9,788,062, the average income of the corn farmer is IDR 5,941,350/ha. Key Word : Corn, farming, and income.